Tuberous Sclerosis Complex-Associated Neuropsychiatric Disorders (TAND): New Findings on Age, Sex, and Genotype in Relation to Intellectual Phenotype - de Vries, Petrus J.; Belousova, Elena; Benedik, Mirjana P.; Carter, Tom; Cottin, Vincent; Curatolo, Paolo; Dahlin, Maria; D'Amato, Lisa; Beaure d'Augères, Guillaume; Ferreira, José C.; Feucht, Martha; Fladrowski, Carla; et al. (Frontiers in Neurology, 2020)
Background: Knowledge is increasing about TSC-Associated Neuropsychiatric Disorders (TAND), but little is known about the potentially confounding effects of intellectual ability (IA) on the rates of TAND across age, sex and genotype. We evaluated TAND in a) children versus adults, b) males versus females, and c) TSC1 versus TSC2 mutations, after stratification for levels of IA, in a large, international cohort. Methods: Individuals of any age with a documented visit for TSC in the 12 months prior to enrolment were included. Frequency and percentages of baseline TAND manifestations were presented by categories of IA (no intellectual disability [ID, intelligence quotient (IQ)>70]; mild ID [IQ:50-70]; moderate-to-profound ID [IQ<50]). Chi-square tests were used to test associations between ID and TAND manifestations. The association between TAND and age (children versus adults), sex (male versus female), and genotype (TSC1 versus TSC2) stratified by IA levels were examined using the Cochran–Mantel–Haenszel tests. Results: 894 of total 2211 participants had formal IQ assessments. There was a significant association (P<0.05) between levels of IA and the majority of TAND manifestations, except impulsivity (P=0.12), overactivity (P=0.26), mood swings (P=0.08), hallucinations (P=0.20), psychosis (P=0.06), depressive disorder (P=0.23) and anxiety disorder (P=0.65). Once controlled for IA, children had higher rates of overactivity, but most behavioural difficulties were higher in adults. At the psychiatric level, attention deficit hyperactivity disorder (ADHD) was seen at higher rates in children while anxiety and depressive disorders were observed at higher rates in adults. Compared to females, males showed significantly higher rates of impulsivity and overactivity, as well as autism spectrum disorder (ASD) and ADHD. No significant age or sex differences were observed for academic difficulties or neuropsychological deficits. After controlling for IA no genotype-TAND associations were observed, except for higher rates of self-injury in individuals with TSC2 mutations. Conclusions: Findings suggest IA as risk marker for most TAND manifestations. We provide the first evidence of male preponderance of ASD and ADHD in individuals with TSC. The study also confirms the association between TSC2 and IA but, once controlling for IA, disproves the previously reported TSC2 association with ASD and with most other TAND manifestations.